Mobile telephony in emerging markets: The importance of dual-SIM phones - Daniel Göller; Kjetil Andersson (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
A substantial share of customers in emerging markets use dual-SIM phones and subscribe to two mobile networks. A primary motive for so called multi-simming is to take advantage of cheap on-net services from both networks. In our modelling effort, we augment the seminal model of competing telephone networks á la Laffont, Rey and Tirole (1998b) by a segment of flexible price hunters that may choose to multi-sim. According to our findings, in equilibrium, the networks set a high off-net price in the linear tariffs to achieve segmentation. This induces the price hunters to multi- sim. We show that increased deployment of dual-SIM phones may induce a mixing equilibrium with high expected on-net prices. Thus, somewhat paradoxically, deployment of a technology that increases substitutability, and thereby competition, may end up raising prices.
Keywords: D43; L13; L96; D43; L13; L96; 330; Network competition; multi-sim; dual-SIM phones; price discrimination